2014
DOI: 10.1261/rna.045310.114
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA profiling and characterization of piRNA clusters in the adult testes of the common marmoset, a model primate

Abstract: Small RNAs mediate gene silencing by binding Argonaute/Piwi proteins to regulate target RNAs. Here, we describe small RNA profiling of the adult testes of Callithrix jacchus, the common marmoset. The most abundant class of small RNAs in the adult testis was piRNAs, although 353 novel miRNAs but few endo-siRNAs were also identified. MARWI, a marmoset homolog of mouse MIWI and a very abundant PIWI in adult testes, associates with piRNAs that show characteristics of mouse pachytene piRNAs. As in other mammals, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 92 publications
(134 reference statements)
14
75
0
Order By: Relevance
“…As in marmoset, we were able to find pachytene clusters that are transcribed divergently from a promoter region shared with a protein-coding gene (Hirano et al 2014): e.g., BUB1, WDR1 as in marmoset and a new instance with TDRD5, which was described neither in mouse nor in marmoset.…”
Section: Definition Of Human Postnatal Prepachytene and Pachytene Pirmentioning
confidence: 69%
See 2 more Smart Citations
“…As in marmoset, we were able to find pachytene clusters that are transcribed divergently from a promoter region shared with a protein-coding gene (Hirano et al 2014): e.g., BUB1, WDR1 as in marmoset and a new instance with TDRD5, which was described neither in mouse nor in marmoset.…”
Section: Definition Of Human Postnatal Prepachytene and Pachytene Pirmentioning
confidence: 69%
“…Notably, as in previous studies on human, marmoset, and mouse small RNAs (Hirano et al 2014;Rounge et al 2015;Kumar et al 2016;Sharma et al 2016), we observed the presence of 31-to 34-nt-long 5 ′ -tiRs (long 5 ′ fragments of tRNAs, Kumar et al 2016). Moreover, using modified bioinformatics pipeline (see Materials and Methods), we were able to detect nontemplated tailing of miRNAs, piRNAs, and 5 ′ -tiRs with different biases for tailed nucleotides and nucleotide combinations (Supplemental Tables S1B, S1B1 and Supplemental Fig.…”
Section: Definition Of Human Postnatal Prepachytene and Pachytene Pirmentioning
confidence: 73%
See 1 more Smart Citation
“…Gene-derived piRNAs were studied in Drosophila, Xenopus, mice, pig and primates including human. [56][57][58][59] However, these studies identify protein-coding genes as piRNA targets computationally with little or without any experimental validation. In contrast, with the analysis of our degradome library we provide the first direct biochemical observation of the actual slicing of protein-coding gene transcripts and TEs mediated by piRNAs in a non-bilaterian animal.…”
Section: Discussionmentioning
confidence: 99%
“…This was true despite the fact that meiotic piRNA clusters were initially reported as being depleted of mobile element sequences as compared with the genome as a whole (Girard et al 2006). However, recent studies have shown that young, potentially active elements are enriched in meiotic piRNA clusters, and these show a bias in orientation such that antisense piRNAs are preferentially produced (Hirano et al 2014;KA Wasik, OH Tam, I Falciatori, SR Knott, M Hammell, VV Vagin, and GJ Hannon, in prep.). Despite strong evidence for LINEs as pachytene piRNA targets, it is unclear whether LINE activation is the root cause of the sterility of MIWI mutants.…”
mentioning
confidence: 98%